A mobile addiction service for community-based overdose prevention - Pepin, Michael D.; Joseph, Jillian K.; Chapman, Brittany P.; McAuliffe, Christina; O’Donnell, Logan K.; Marano, Ryan L.; Carreiro, Stephanie P.; Garcia, Erik J.; Silk, Hugh; Babu, Kavita M. (Frontiers in Public Health, 2023)
Mainstays of opioid overdose prevention include medications for opioid use disorder (e.g., methadone or buprenorphine) and naloxone distribution. Unfortunately, inadequate access to these lifesaving therapies limits their uptake, especially in communities of color. Moreover, people with opioid use disorders encounter multiple barriers to obtaining necessary medications, including insurance, transportation, and consistent availability of telephones. The University of Massachusetts Medical Center and our community partners sought to alleviate these barriers to treatment through the deployment of a mobile addiction service, called the Road to Care. Using this approach, multidisciplinary and interprofessional providers deliver holistic addiction care by centering our patients’ needs with respect to scheduling, location, and convenience. This program also extends access to buprenorphine and naloxone among people experiencing homelessness. Our experience demonstrates that a community-based mobile addiction service, anchored within a major medical center, can provide high-volume and high-quality overdose prevention services that facilitate engagement with additional treatment.